TRANSFORMATION VS LIVING HERITAGE : VALUE SPACE REGENERATION FOR GEORGE TOWN CITY - Robert Sitorus; Sibarani Sofian (Universitas Sains dan Teknologi Jayapura, 2013)
The dynamic history of George Town in Penang Island formerly created by different cultures and people makes a unique identity for this town. From the 17th century, British, Jewish, Chinese, and Malay people as local ethnic from Penang Island have contributed and merged their own cultures, resulting in the multi-cultural society of Penang Island. This phenomenon shows how Penangites acceptance and the ability in adopting new values and cultures from foreign people. However, once a economic and cultural center of Southeast Asia, Penang is facing competition in various sectors, especially electronics and industry, due to lost competitiveness in global stage, exodus of talents, scarcity of land and higher economic cost. George Town, in particular, being the cultural and heritage heart of the island, is facing even greater challenge as the core of the city is hollowing out and now in state of severe social, environmental and economic decline. The core area has become underutilized despite it’s wealth of beautiful heritage buildings. This is alarming given the fact that George Town, along with Malacca, is being considered for UNESCO World Heritage Site status this year. Contributing to the urban decay is the overall loss of economic life in the core area as unique stalls, restaurants and small business owners are diminishing. There is a great hope that George Town can be transformed and re-gain it’s role as cultural and creative hub of Asia. The city has already been the base of technological industry (Intel, Dell, Microsoft). The city’s diversity of culture, ample source of talents, strong identity and organizational culture provide ideal setting and necessary elements to attract creative class and entrepreneurs to come and set up business and industry. The city needs to organize itself and provide the right policy and implement strategic change. In this paper, we wish to share the case study of transforming and revitalizing George Town by repositioning it self as creative center while recognizing culture as its greatest asset and ensuring that new developments do not compromise old values. The effort is initiated by Khazanah National, a government linked corporation which invited EDAW as lead consultant in Economic, Planning and Environment discipline, Scott Wilson as Traffic Engineer, Badan Warisan as heritage advisor of the city. Lawrence Loh architect and Charles Landry are two leading experts being the advisors of the projects. This paper primarily focus on socio-economic and cultural aspect, market trends in Penang, UNESCO world heritage status impact, assets-obstacles and Northern Corridor Economic Region (NCER) context. The approaches for the project is more empirical and based on data gathering, interview with key prominent person or institution and finally involve analysis of historical research to examining the past to find solutions for the present. This paper presented George Town Transformation as an ongoing process and not a final result. Due to the length of the project, lack of information and on ground research, a lot of assumptions were taken and still many outstanding issues to be explored further.